Cube Duel : 2 Player Puzzle Game + Bonus 80 1 player challenges - SmartGames (Kontich : SmartGames, 2018)
Daag je tegenstander uit en plaats de rode of gele stukken strategisch zodat de kubus meer van uw kleur bovenop heeft! Speel je alleen? Ontwikkel dan jouw 3D-bouwvaardigheden met behulp van de 80 uitdagingen. De spelregels zitten in de doos.
Red vs yellow, get your colour on top! Challenge your opponent and strategically place the red or yellow pieces so that the cube has more of your color on top! Playing alone? Then develop your 3D building skills using the 80 challenges. Game rules included.
Keywords: Strategie; Gezelschapsspellen